PENGEMBANGAN SISTEM INFORMASI PERENCANAAN PEMBANGUNAN SEBAGAI PEMROSESAN TRANSAKSI PADA MUSRENBANG TINGKAT KELURAHAN KOTA SEMARANG - Fahmi Amiq (Semantik, 2011)
Development planning system is a unified regional planning procedure to produce development plans for the long term, medium term, and annual. Development Planning Consultation (Musrenbang) Village is a district annual planning forum to discuss and agree on the proposed development activities Musrenbang results at RT and RW are the real problem identification for the preparation of the proposed activity of the needs of village level development using the principles of participatory, sustainable and comprehensive. Development Planning Information System Development as transaction processing at village level Musrenbang using the linear sequential model (SDLC method). The result of the development is an information system development planning as transaction processing that can be used to collect, store, process data acquisition, control decisions and is able to produce information such as reports, documents and other relevant outputs, so that planning and implementation of development may be optimized and meet development targets according to the scale of priority the achievement and fulfilling aspect of accountability in realizing good governance.Keywords :Information system, Musrenbang, RT, RW, Kelurahan